The Ror-Family Receptors in Development, Tissue Regeneration and Age-Related Disease - Endo, Mitsuharu; Kamizaki, Koki; Minami, Yasuhiro (Frontiers in Cell and Developmental Biology, 2022)
The Ror-family proteins, Ror1 and Ror2, act as receptors or co-receptors for Wnt5a and its related Wnt proteins to activate non-canonical Wnt signaling. Ror1 and/or Ror2-mediated signaling plays essential roles in regulating cell polarity, migration, proliferation and differentiation during developmental morphogenesis, tissue-/organo-genesis and regeneration of adult tissues following injury. Ror1 and Ror2 are expressed abundantly in developing tissues in an overlapping, yet distinct manner, and their expression in adult tissues is restricted to specific cell types such as tissue stem/progenitor cells. Expression levels of Ror1 and/or Ror2 in the adult tissues are increased following injury, thereby promoting regeneration or repair of these injured tissues. On the other hand, disruption of Wnt5a-Ror2 signaling is implicated in senescence of tissue stem/progenitor cells that is related to the impaired regeneration capacity of aged tissues. In fact, Ror1 and Ror2 are implicated in age-related diseases, including tissue fibrosis, arteriosclerosis, neurodegenerative diseases, and cancers. In these diseases, enhanced and/or sustained (chronic) expression of Ror1 and/or Ror2 is observed, and they might contribute to the progression of these diseases through Wnt5a-dependent and -independent manners. In this article, we overview recent advances in our understanding of the roles of Ror1 and Ror2-mediated signaling in the development, tissue regeneration and age-related diseases, and discuss their potential to be therapeutic targets for chronic inflammatory diseases and cancers.